Management of high-risk Myeloma: an evidence-based review of treatment strategies - Giesen, Nicola; Goldschmidt, Hartmut; Raab, Marc-Steffen (Expert review of hematology, 2016)
Introduction: Despite the progress made in the treatment of patients with multiple myeloma over recent decades, a significant cohort with high-risk disease as defined by specific clinical and genetic criteria continue to respond poorly to standard treatment. These patients represent a particular challenge to the treating physician and require early identification as well as personalized treatment strategies.Areas covered: In this review, we discuss the prognostic impact of adverse clinical, radiological and genetic factors, evaluate available scoring systems and highlight key aspects of the therapeutic management of high-risk myeloma. MEDLINE and recent scientific meetings’ databases were searched for the keywords ‘high-risk’ and ‘multiple myeloma’ and relevant studies relating to both diagnostic and therapeutic approaches were identified.Expert commentary: A case is made for intensive induction using combinations of novel agents, early high-dose therapy supported by autologous stem cell transplantation and the widespread use of maintenance therapies. Novel therapeutic options, especially in the field of immunotherapy, are currently explored in clinical trials and have the potential to further improve outcomes for patients with high-risk multiple myeloma.